Mg2+ storage and mobility in anatase TiO2: the role of frustrated coordination. Issue 8 (30th January 2019) - McColl, Kit; Corà, Furio
Abstract : Low migration barriers of ∼540 meV allow good Mg mobility under dilute conditions, but cooperative lattice distortions limit mobility at high Mg concentrations. Abstract : Anatase TiO2 is a candidate high-power electrode material in Li-ion and Na-ion batteries and has been explored as a Mg battery cathode material, although Mg capacity in undoped anatase is limited. Here we use hybrid-exchange density functional theory calculations to investigate the underlying factors affecting Mg intercalation and mobility in anatase. We find that at the dilute limit, Mg ions have 5-fold coordinated insertion sites, and activation barriers for migration are a surprisingly low 537 meV. As the concentration of Mg inserted into the structure is increased, a cooperative distortion of the lattice occurs, contracting the c lattice parameter. The distortion results in stable orderings of Mg ions in sites which are 6-fold coordinated, but also results in migration barriers that exceed 1500 meV in Mg0.5 TiO2 due to a collective relaxation of the host lattice. The total increase in barrier is predominantly a result of the stabilisation of the insertion sites, as opposed to a destabilisation of the activated sites along the migration pathway. The insertion sites in the dilute limit can be described as frustrated, and it is this unfavourable insertion geometry under dilute conditions that allows the Mg ions to migrate with low activation barriers. The limited performance for Mg 2+ storage can therefore be attributed to the loss of frustrated coordination at high Mg concentration, which restricts Mg mobility and therefore capacity. Strategies to enhance the capacity of Mg in anatase should therefore aim to inhibit the c lattice parameter contraction or otherwise destabilise stable orderings of Mg in Mg0.5 TiO2 to retain the frustrated coordination of Mg ions at high Mg concentrations.